(untitled) (American Journal of Islam and Society, 2008)
Gabriele Marranci’s latest book, The Anthropology of Islam, examines the history and current status of anthropological work focusing on Islam. Despite its title, this work seems less intended as an overview of the anthropology of Islamthan as a critique of the field. Essentialism,Marranci argues, still marks prominent works of anthropology that focus onMuslims. Edward Said’s critique of Orientalism and anthropology’s post-1980s “crisis of representation” notwithstanding, Islam and Muslims are still represented in many anthropological texts as fixed and unchanging, tethered to an imagined, unitary tradition. Anthropological studies have not yet caught up with the impact of migration, the Internet, or other global processes, and thus they represent Muslims abroad as caught between cultures or locked in an inevitable crisis of identity in which a rigidly defined faith is found to be at odds with the pluralism of western life. The approach Marranci advocates involves examining the diverse ways Muslims feel and experience their religion, as well as the complex networks and interactions in which they locate themselves, particularly in the West. “‘Muslim,’” he writes, “has an emotional component attached to it. They feel to be Muslim. Then, and only then, the ‘feeling to be’ is rationalized, rhetoricized, and symbolized, exchanged, discussed, ritualized, orthodoxized or orthopraxized” (p. 8). Drawing on cognitive neuroscience, the author advocates exploring identity practices through this “feeling to be” Muslim ...